Tourism Students’ Perception towards English as their Foreign Language in Indonesia - Anam, Mochammad Musafa'ul (UIBU, 2025)
In this global era, English is not only spoken by the native speaker of English. It plays as an essential role in many aspects such as academic, sciences, literatures, music, as well as tourism industry. One of the countries that use English for its’ educational and tourism sector is Indonesia. This study is aiming to identify the Indonesians of Tourism Students’ perception towards English language as their foreign language. this study employed a quantitative approach that used questionnaire as its’ main data colleting instrument. The total of population of this study were 111 students of Program Diploma Kepariwisataan, University of Merdeka Malang. The result of this study found that there is no clear relationship between the learning duration and language acceptance of the students. The English language improvement can be obtained through a comprehensive development of pedagogical, psychological and institutional aspect. It needs an integrated-complete skill of English such as listening, speaking, reading and writing. By having such supportive environment, students are expected to understand more effectively and perform English with no doubt.